2022
DOI: 10.22159/ijap.2022v14i2.43783
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Factorial Design to Optimize the Formulation Method of Ezetimibe Polymeric Nanoparticle by Homogenization Cum Ultra-Sonication Method

Abstract: Objective: The objective of this study is to use a 23 factorial design to optimize the formulation factors of Ezetimibe polymeric nanoparticle. Methods: By varying formulation variables such as polymer concentration (hydroxyl propyl methyl cellulose composition) and process variables such as homogenization time (min) and ultra-sonication time, the formulation of polymeric nanoparticles was designed using a 23 factorial design and prepared using the homogenization cum ultra-sonication method (min). Particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another study demonstrated that polymer-encapsulated luteolin nanoparticles were tested against Tu212 and H292 cell lines and demonstrated a more potent anticancer effect than luteolin alone due to the target tumour receptor binding with the target ligand on the nanoparticle surface and demonstrating over-expressing tumour activity [6]. It also studied that Febuxostat nanosuspension prepared by lyophilization techniques exhibited an enhanced solubility and oral bioavailability [4,7]. Nanoresveratols formulated by Cyclodextrin-based nanosponges enhance water solubility and stability, and liposome nano resveratrol showed excellent cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that polymer-encapsulated luteolin nanoparticles were tested against Tu212 and H292 cell lines and demonstrated a more potent anticancer effect than luteolin alone due to the target tumour receptor binding with the target ligand on the nanoparticle surface and demonstrating over-expressing tumour activity [6]. It also studied that Febuxostat nanosuspension prepared by lyophilization techniques exhibited an enhanced solubility and oral bioavailability [4,7]. Nanoresveratols formulated by Cyclodextrin-based nanosponges enhance water solubility and stability, and liposome nano resveratrol showed excellent cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoresveratols formulated by Cyclodextrin-based nanosponges enhance water solubility and stability, and liposome nano resveratrol showed excellent cell proliferation. Resveratrol nanosuspension increase solubility rate and antioxidant potential [7,8]. We examined three English databases, including Web of Science, Google Scholar, and PubMed, for papers published over the last five years that discussed the various approaches used to encapsulate phytochemicals with a nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Some medications are absorbed from the mouth, pharynx, and esophagus as the saliva passes down into the stomach [7,8]. Polymeric nanoparticles (NPs) are one of the most commonly employed nanomaterials in nanomedicine because they can deliver a drug to a specific region of an organ with a lower dose, hence increasing drug bioavailability at the desired target [9]. Amlodipine is a dihydropyridine calcium channel antagonist introduced for treating hypertension, coronary heart failure, and certain types of angina.…”
Section: Introductionmentioning
confidence: 99%